2018
DOI: 10.1167/iovs.17-23454
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Origin of the Ocular Pulse and Its Impact on the Optic Nerve Head

Abstract: Our models indicate that, during the cardiac cycle, the OPA and choroidal expansion can deform the ONH with a net shearing of neural tissues within the neuroretinal rim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 89 publications
0
29
0
Order By: Relevance
“…Using FE modelling, we previously modelled the origin of the ocular pulse and its effect on the ONH. 19 We found that a change in arterial pressure (as that occurring from diastole to systole) resulted in choroidal swelling, which in turn induced a change in IOP (the OPA) due to the incompressibility of the vitreous. Both the OPA and choroidal swelling were responsible for deforming the ONH tissues, and a relatively large shearing of neural tissues was observed within the neuroretinal rim.…”
Section: Methodsmentioning
confidence: 80%
See 4 more Smart Citations
“…Using FE modelling, we previously modelled the origin of the ocular pulse and its effect on the ONH. 19 We found that a change in arterial pressure (as that occurring from diastole to systole) resulted in choroidal swelling, which in turn induced a change in IOP (the OPA) due to the incompressibility of the vitreous. Both the OPA and choroidal swelling were responsible for deforming the ONH tissues, and a relatively large shearing of neural tissues was observed within the neuroretinal rim.…”
Section: Methodsmentioning
confidence: 80%
“…The geometry of the three-dimensional eye model was adapted from our previous studies. 12, 19, 24 In summary, the eye globe and optic nerve were reconstructed from magnetic resonance imaging images of a heathy subject. The corneoscleral shell was assumed to be spherical with an outer diameter of 24 mm and thickness of 1 mm.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations